Plasma microRNA192 in combination with serum CA19-9 as non-invasive prognostic biomarker in periampullary carcinoma. Issue 3 (March 2017) - Murali Manohar, K; Sasikala, Mitnala; KVSRR, Yesaswini; Sunil, V; Talukdar, Rupjyoti; Murthy, HVV; Ramji, C; Rao, GV; Pradeep, R; Reddy, D Nageshwar
In this study, circulating microRNAs (miRNAs) are being investigated as non-invasive biomarkers for early diagnosis and prognosis of human cancers. Since the prognosis for pancreatobiliary subtype of periampullary carcinoma is poor, we assessed the prognostic relevance of miRNAs in combination with CA19-9 as noninvasive biomarker in periampullary carcinoma. Circulating miRNAs in plasma and serum CA19-9 were evaluated in periampullary carcinoma patients (n = 109) undergoing Whipple's pancreaticoduodenectomy and in healthy volunteers (n = 92). Tumour tissues were subjected to staging and subtyping prior to determining differentially expressed miRNAs in them by quantitative real-time polymerase chain reaction (qRT-PCR). Statistical analysis involved correlation, receiver operating characteristic, logistic regression, survival analyses and Cox-proportional regression. Of the three differentially expressed circulating miRNA, miRNA192 was significantly increased both in circulation and in tumour tissue and correlated with tumour stage and aggressiveness (r = 0.96, P < 0.0001). Area under the curve of circulating miRNA192 + CA19-9 combination was 0.877 (95% confidence interval, 0.72 to 0.96) for stage III and 0.92 (95% confidence interval, 0.77 to 0.88) for tumour aggressiveness. The combination was associated with poor survival (median: 22 months, P = 0.0008) in stage III patients. Cox-proportional regression analysis revealed prognostic importance of combination of circulating miR192 and CA19-9 (HR = 1.005, P = 0.0001) in periampullary carcinoma. In conclusion, combination of circulating miRNA192 with serum CA19-9 is a better prognostic biomarker than CA19-9 alone.